Expansion of interferon-γ-secreting HIV-specific T cells during successful antiretroviral therapy. - Gasser, O; Brander, C; Wolbers, M; Brown, N; Rauch, A; Günthard, H; Battegay, M; Hess, C (2013)
OBJECTIVES: Antiretroviral therapy (ART) suppresses HIV viraemia, thereby reducing the antigenic drive for T cells to proliferate. Accordingly, selected HIV-specific T-cell responses have been described to contract within weeks of ART initiation. Here, we sought to investigate whether these findings apply to the entire repertoire of HIV-specific T cells. METHODS: Using interferon (IFN)-γ enzyme linked immuno spot (ELISpot), we performed retrospective 2-year proteome-wide monitoring of HIV-specific T cells in 17 individuals with undetectable viral loads during ART. The sample pool for each study subject consisted of one pre-ART time-point and at least two time-points after initiation of therapy. RESULTS: Peripheral pools of HIV-specific T cells decreased nonsignificantly within the first 2 years under ART in our cohort of patients, in terms of both breadth and magnitude. However, in most cases, the seeming decrease masked ongoing expansion of individual HIV-specific T-cell responses. We detected synchronous contraction and expansion of T-cell responses - with different peptide specificities - in 12 out of 17 study participants during follow-up. Importantly, the observed expansions and contractions of individual HIV-specific T-cell responses reached similar ranges, supporting the biological relevance of our findings. CONCLUSIONS: We conclude that successful ART enables both contraction and expansion of HIV-specific T-cell responses. Our results should prompt a renewed interest in HIV-specific T-cell dynamics under ART, in particular to elucidate the mechanisms that uncouple, to some extent, particular HIV-specific T-cell responses from variations in circulating antigen load and functionally characterize expanding/contracting T-cell populations beyond IFN-γ secretion. Assuming that expanding HIV-specific T-cell responses under ART are protective and functional, harnessing those mechanisms may provide novel opportunities for assisting viral control in chronically infected individuals.